INSTITUTIONALIZATION OF THE COLLECTIVE MEMORY OF THE TAIPAS / FRATERNITIES IN THE POST-CONFLICT CHECHEN REPUBLIC - Osmaev, Abbaz Dogievic; Gorusina, Evgenia Mihajlovna (History, Archeology and Ethnography of the Caucasus, 2023)
This article discusses the formation of collective memory within Chechen tayps, focusing on the underlying mechanisms of this process. It investigates the development of tayp identity and the preservation of traditions in the post-conflict era of the Chechen Republic. The study employs content analysis of 24 sources related to Chechen tayps. The objective is to explore the collective memory of tayps, which underwent significant changes from the Late Middle Ages to the first half of the 19th century, yet remains a steadfast marker of Chechen identity. The subject of investigation is the mechanism of creating, altering, and transmitting collective memory within a tayp. Historically, the formation of tayps’ collective memory relied heavily on oral sources. However, as a result of the deportation of 1944 and the subsequent political crisis in the late 20th and early 21st centuries, tayps experienced substantial loss of their traditional material culture and were partially or completely disconnected from their original places of residence. During the post-conflict restoration period of the Chechen Republic, there has been a renewed interest in the history, genealogy, and societal role of tayps. While oral sources were previously sufficient for transmitting this knowledge, the growing public demand has led to an increase in scientific and journalistic publications. The institutionalization of tayp’s collective memory in modern Chechen society is achieved through the publication of books, essays, and articles about its history, the establishment of internet sites and social media groups, as well as the revival of ancestral towers and villages abandoned in 1944. To strengthen the tayp identity among its members, modern communication tools are utilized, enabling them to maintain contact regardless of their geographical location or country of residence.
Keywords: collective memory; group; tayp; institutionalization; Chechen Republic; crisis; post-conflict era